The Effect of Non-Seasonal Climate Variations on Extreme Rainfall Events in Early Rainy Season Onset in Southest West Java Province - Agus Safril; Hadi Saputra; Siswanto Siswanto; Aulia Nisaul Khoir; Aditya Kusuma Al Arif (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2020)
The region of Tasikmalaya, Garut, and Pangandaran (hereafter mentioned as Southeast West Java Province) experienced extreme precipitation that occurred on September 16, 2016, October 6, 2017, and November 5, 2018, which then followed by flood. The characteristics of these extreme rainfall events need to be communicated to the related disaster management agency and the local citizens as a part of understanding the risks and disaster mitigation. This paper aims to determine the relation between extreme rainfall and non-seasonal climate variations such as Madden Julian Oscillation (MJO), El NiÃ±o Southern Oscillation (ENSO), tropical storm, and local circulation that occur simultaneously. Atmosphere and ocean data, including daily rainfall, precipitable water, cloud satellite imagery, wind and sea surface temperature were used. Descriptive statistical analysis, atmospheric dynamics, and physical atmosphere were applied to characterize the event, spatially and temporally. The results showed that the MJO was a non-seasonal factor that always exists in these three early rainy season extreme rainfall events in the region. Other non-seasonal factors such as interaction between La Nina and tropical disturbance; La Nina and local circulation; and El Nino and local circulation also affected the extreme rainfall events. We conclude that the intra-seasonal climate variation of MJO and inter-annual climate anomaly of La Nina/ El Nino, tropical storm, and local circulation are among the weather generators for extreme rainfall during early rainy season (September to November) in the Southeast West Java Province.